Characterization of Microarchitectures, Stiffness and Strength of Human Trabecular Bone Using Micro-Computed Tomography (Micro-CT) Scans - Ahmed Sherif El-Gizawy; Xuewei Ma; Ferris Pfeiffer; James D. Schiffbauer; Tara Selly (BioMed, 2023)
The present work presents evaluation and experimental verification of the use of X-ray computed tomographic microscopy (micro-CT) for accurate characterization of geometry, microarchitecture, and stiffness properties of bones. These properties are crucial for designing and building optimized implants for joint and dental reconstruction applications. High-resolution micro-CT scans would provide more detailed and accurate information about the microarchitecture and density distribution across patient bones. Nevertheless, micro-CT applications on live patients require invasive procedures involving small bone biopsy specimens. Alternatively, micro-CT could be used on samples collected from selected cadavers of different age, gender, and race groups to establish a database that could be used for providing useful microarchitecture information. The micro-CT scans of investigated bone samples reveal that the trabecular bone is anisotropic and heterogeneous. The results also showed considerable degree of parametric variability and uncertainty on microarchitecture and stiffness properties of patient’s trabecular bone.